2014
DOI: 10.1186/2051-6673-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Body self-evaluation and physical scars in patients with borderline personality disorder: an observational study

Abstract: BackgroundData from general psychology suggest that body self-evaluation is linked to self-esteem and social emotions. Although these emotions are fragile in individuals with borderline personality disorder (BPD), body self-evaluation is clearly understudied in BPD research.MethodsA total of 200 women took part in the study: 80 female BPD patients, and 47 healthy and 73 clinical controls including post-traumatic stress disorder (PTSD) after childhood sexual abuse (CSA). Diagnoses were established through stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
(42 reference statements)
3
26
0
Order By: Relevance
“…Firstly, our results regarding body evaluation in the cBPD group confirm previous findings which reported that the overall body image is negative in women with a current BPD (Haaf et al, 2001;Kleindienst et al, 2014;Sansone, Chu, & Wiederman, 2010;Sansone, Wiederman, & Monteith, 2001). In addition, our results correspond to those from previous studies hereby confirming that body evaluation in the group of cBPD is in sharp contrast to mentally healthy women who typically reported a positive attititude towards their own body (Haaf et al, 2001;Kleindienst et al, 2014). However, the separate analyes of sexually connoted and neutral body areas revealed that the overall neagtive evaluation in cBPD might be driven by a negative evaluation of the sexually connoted body areas wheras neutral body areas were evaluated as neutral in cBPD.…”
Section: Discussionsupporting
confidence: 90%
“…Firstly, our results regarding body evaluation in the cBPD group confirm previous findings which reported that the overall body image is negative in women with a current BPD (Haaf et al, 2001;Kleindienst et al, 2014;Sansone, Chu, & Wiederman, 2010;Sansone, Wiederman, & Monteith, 2001). In addition, our results correspond to those from previous studies hereby confirming that body evaluation in the group of cBPD is in sharp contrast to mentally healthy women who typically reported a positive attititude towards their own body (Haaf et al, 2001;Kleindienst et al, 2014). However, the separate analyes of sexually connoted and neutral body areas revealed that the overall neagtive evaluation in cBPD might be driven by a negative evaluation of the sexually connoted body areas wheras neutral body areas were evaluated as neutral in cBPD.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Kleindienst et al (2014) corroborated this connection in a sample of women with borderline personality disorder (BPD). Results showed that the presence of physical scars was significantly related to negative feelings toward one's body (Kleindienst et al, 2014). Whereas Kleindienst et al assessed all physical scars, the current study solely focuses on the overall meaning and subjective importance of NSSI scars.…”
mentioning
confidence: 64%
“…Incorporating a mindful approach to exploring the sensations, thoughts, and feelings that arise when attending to self-injury scars may help the client explore meaning without placing judgment and begin cognitively reducing or restructuring the shame and negative meaning resulting from the scar (Bowen et al, 2010;Segal et al, 2013). Relatedly, using an acceptance and nonjudgmental approach to addressing negative body image of scarred body locations (e.g., in Kleindienst et al, 2014) may help with creating a sense of personal growth and sustaining treatment gains. Also, mindfulness techniques presented in Dialectical Behavior Therapy may be beneficial in helping a client learn to take a nonjudgmental and nonevaluative approach in exploring the meaning behind the self-injury scar, thereby finding synthesis between acceptance of the scar and change of future behaviors (Linehan, 2014).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, a more comprehensive assessment battery is needed to provide a more complete assessment of the patients' problems related to BPD. In particular, assessments reflecting the subjective experiences of the patients, including quality of life and aspects of well-being such as self-esteem, a positive evaluation of the own body [44], and connectedness [45][46] would add value and clinical meaning to the classes of symptom severity.…”
Section: Resultsmentioning
confidence: 99%